Multistage Genetic Algorithm and Q-learning for Flexible Ligand-Protein Docking - Marlisah, Erzam; Yaakob, Razali; Nasir Sulaiman, Md.; Basyaruddin Abdul Rahman, Mohd; N. Shah Zainudin, M. (International Journal of Engineering and Technology, 2018)
Protein-ligand docking is an optimization task involving translation and rotation of orientation and torsional angles of a small molecule (ligand) with respect to a target protein. Traditional genetic algorithm can be used to find the optimal conformation, however it often found poor structure with high docked energy due to premature convergence and its weakness in performing precision search. The proposed algorithm is a multistage genetic algorithm with Q-learning agent to overcome the limitations inherent in genetic algorithm and reinforcement learning algorithm. The idea is to combine the explorative speed of genetic algorithm in finding promising area in the search space and the ability of the reinforcement learning agent to do fine-grained search. Docking of ten ligands to thermolysin as the target protein shows the proposed algorithm is more efficient in finding the lowest docked energies and more reliable in finding similar structure every run compared to traditional genetic algorithm and AutoDock Vina in docking highly flexible ligand. The algorithm almost matches AutoDockÂ  Vina in docking less flexible ligands and outperforms it in docking highly flexible ligands.Â Â